Avaliação da resistência adesiva entre um cimento resinoso e ligas para metalo-cerâmica submetidas a dois diferentes condicionamentos de supefície - Andreatta Filho, Osvaldo Daniel [UNESP] (2005)
The aim of this study is to evaluate the hypothesis that different conditionings of surface of three dental alloys (Gold - Degudent U – Degussa; Nickel-chromium - Wiron 99, Bego; Titanium - Rematitan, Dentaurum) they do not modify the values of bond strength with a resin cement. Twenty blocks of each alloy with dimensions of 5x5x5mm were cast and divided in two subgroups of 10 blocks that were conditioned with the following surface treatments: TRAT. 1 – sandblasting with particles of oxide of aluminum 110μm (Al2O3) + Alloy Primer (Kuraray, CO) and TRAT. 2 - sandblasting with particles of oxide of silica with Cojet-Sand (3M/ESPE) + Silane (ESPE-SIL). The conditioned blocks of each group were luted with Panavia F (Kuraray, CO) to composite resin blocks of ClearfilTM AP-X (Kuraray, CO) under constant load of 750g for 10 minutes. Six experimental groups were constituted by sets formed by the alloy, cement and composite resin. The sets were split up in a mechanical lathe obtaining by block 4 samples with dimensions of 10x1x1mm and the adhesive surface with approximately 1mm2. The microtensile test was accomplished in an universal test machine (EMIC) with cell of load of 10kgf and crosshead speed of 1mm/min. Each group was represented by forty samples, however each group presented 10 means values of bond strength MPa (n=10), obtained from the mean of the individual values of the four samples of each cemented blocks. Means and standard deviation of bond strength (MPa) were: G1: 7.33 ± 1.93d; G2: 13.35 ± 2.18 c G3: 23.56 ± 6.5 b; G4:42.6 ± 5.84 a; G5: 26.17 ± 1.94 b; G6: 44.30 ± 2.3 a. The data of bond strength were analyzed by the analysis of variance test (ANOVA) and Tukey test, p<0.05. The results indicated that surface treatment 2 (Cojet) increased the bond strength between the resin cement and alloys. The smallest values of bond strength were obtained with gold alloy, independent of ....